'Anti-extortion' mechanism of indigenous innovation by technologically backward firms: evidence from China. Issue 5 (4th May 2021) - Jin, Yuhuan; Zhang, Sheng; Bigus, Jochen
ABSTRACT: Aiming at the strategic behaviour in 'technology make-or-buy decisions' in the real economy, this study develops a Cournot competition model with endogenous technological level, by comparing the technology acquisition cost of technologically backward firms under different technology acquisition strategies, we theoretically analysed the 'anti-extortion' mechanism of indigenous innovation by technologically backward firms, and the relationship between indigenous innovation and technology imports is empirically tested by using the data of Chinese industrial enterprises above designated size. We show that indigenous innovation can significantly enhance a firm's bargaining power, and the technology acquisition strategy of simultaneous technology imports and indigenous innovation can not only reduce the technology imports cost but also reduce the indigenous innovation cost. Therefore, only by indigenous innovation based on technology imports, can firms enhance their market competitiveness.